2016
DOI: 10.1080/09593330.2016.1245361
|View full text |Cite
|
Sign up to set email alerts
|

Water treatment with exceptional virus inactivation using activated carbon modified with silver (Ag) and copper oxide (CuO) nanoparticles

Abstract: Continuous flow experiments (450 mL min) were performed in household filter in order to investigate the removal and/or inactivation of T4 bacteriophage, using granular activated carbon (GAC) modified with silver and/or copper oxide nanoparticles at different concentrations. GAC and modified GAC were characterized by X-ray diffractometry, specific surface area, pore size and volume, pore average diameter, scanning electron microscopy, transmission electron microscopy, zeta potential and atomic absorption spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 82 publications
1
37
0
2
Order By: Relevance
“…The Escherichia coli bacteria solution was homogenized and then fed to the top of the filtration column (0.075 m of diameter and 0.085 m of height, with a volume of 0.000 38 m 3 ), with the aid of a peristaltic pump, in a constant flow of ∼500 mL/min. The column was filled with ∼200 g of the material produced, a volume of 10 L of solution, with an approximate concentration of 10 9 CFU/L was percolated in each experiment. The sample was collected at the end of the filtration (10 L) and the bacteria was quantified to determine the efficiency of the material produced.…”
Section: Methodsmentioning
confidence: 99%
“…The Escherichia coli bacteria solution was homogenized and then fed to the top of the filtration column (0.075 m of diameter and 0.085 m of height, with a volume of 0.000 38 m 3 ), with the aid of a peristaltic pump, in a constant flow of ∼500 mL/min. The column was filled with ∼200 g of the material produced, a volume of 10 L of solution, with an approximate concentration of 10 9 CFU/L was percolated in each experiment. The sample was collected at the end of the filtration (10 L) and the bacteria was quantified to determine the efficiency of the material produced.…”
Section: Methodsmentioning
confidence: 99%
“… Schmitz et al (2016) Activated carbon modified with silver and copper oxide nanoparticles Bacteriophage T4 The modified porous media was able to achieve virus reduction in the region of Log 3. Shimabuku et al (2017) Iron electrocoagulation – microfiltration Bacteriophage MS2 The primary mechanism was by sweep flocculation which was assisted by charge neutralization. Tanneru and Chellam (2012) Nano-Titanium oxide membrane adsorption Bacteriophage F2 PAN (0.05 μm) membrane had higher removal efficiency than PVDF (0.20 μm) membrane.…”
Section: Management and Mitigation Strategiesmentioning
confidence: 99%
“…These are only relevant to larger cities where such treatment plants are in place. Though studies have shown that the utilization of silver in the virus de-contamination of water is of advantage like for photocatalytic degradation ( Liga et al, 2011 ), adsorption column ( Shimabuku et al, 2017 ) and ceramic pot filtration ( Van der Laan et al, 2014 ), these would be rather expensive solutions for developing countries especially when implementation is on a large scale.…”
Section: Management and Mitigation Strategiesmentioning
confidence: 99%
“…While the presence of SARS-CoV-2 in wastewater have been studied and confirmed, 15 , 16 , 17 , 18 only a few studies have so far investigated its persistence in the wastewater environment, 19 thereby creating an important information gap on the provision of sustainable approaches to mitigate the spread of the virus through this medium. Moreover, the previous knowledge on the virus removal methods, deactivation/inactivation, and treatment 20 , 21 , 22 can be further explored targeting the novel SARS-CoV-2. Therefore, it is important to review recent advances in wastewater treatment and the protection of wastewater plant personnel in the face of the pandemic and proffer effective techniques.…”
Section: Introductionmentioning
confidence: 99%